Over the mountains and far away : studies in near Eastern history and archaeology presented to Mirjo Salvini on the occasion of his 80th birthday - Salvini, Mirjo; Avetisyan, P. S. 1957-; Dan, Roberto; Grekyan, Yervand H. (Archaeopress Publishing Ltd, 2019)
The publication of 'Over the Mountains and Far Away' was initiated by the Institute of Archaeology and Ethnography, National Academy of Sciences of Armenia, the International Association of Mediterranean and Oriental Studies (Rome, Italy) and the Association for Near Eastern and Caucasian Studies (Yerevan, Armenia) as a tribute to the career of Professor Mirjo Salvini on the occasion his 80th birthday. It is composed of 62 papers written by his colleagues and students from Italy, Germany, France, Spain, Poland, the Netherlands, Denmark, Austria, Great Britain, Russian Federation, Israel, Turkey, Islamic Republic of Iran, Georgia, United States and Armenia. The contributions presented here cover numerous topics, a wide geographical area and a long chronological period.